2018
DOI: 10.1111/nep.13083
|View full text |Cite
|
Sign up to set email alerts
|

Impact of end‐stage renal disease in children on their parents

Abstract: The PedsQL™ FIM appears to be a useful tool for the assessment of family impact on children with ESRD. Further prospective studies focused on the QOL of parents and caregivers should be performed with the goal of improving clinical outcomes for pediatric ESRD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 20 publications
1
20
1
Order By: Relevance
“…This phenomenon is called "response shift" which means that with passage of time caregivers learned how to cope with and adjust to their child illness and thus report better QoL [33]. In contrast to our results, a study of family impact of children with ESRD revealed higher scores of the PedsQL™ FIM with short duration (< 5 years) than longer duration (≥ 5 years) [23]. This result suggests that a longer duration of ESRD can impose additional burden on parents or caregivers especially when their children reach end-stage of the disease.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This phenomenon is called "response shift" which means that with passage of time caregivers learned how to cope with and adjust to their child illness and thus report better QoL [33]. In contrast to our results, a study of family impact of children with ESRD revealed higher scores of the PedsQL™ FIM with short duration (< 5 years) than longer duration (≥ 5 years) [23]. This result suggests that a longer duration of ESRD can impose additional burden on parents or caregivers especially when their children reach end-stage of the disease.…”
Section: Discussioncontrasting
confidence: 99%
“…Because most patients with CKD especially children need comprehensive support and care, their caregivers feel more physical, psychological, and financial stress. Unfortunately, few studies have been conducted to measure the QoL of caregivers of children with CKD [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we concluded that pediatric patients on PD had a better QOL in comparison to pediatric patients on HD according to the parent proxy-reports. This conclusion is similar to a Korean study of 79 ESRD pediatric patients aged 8 to 18 years using the PedsQL TM 3.0 ESRD Module and PedsQLTM FIM questionnaires 10. The parent reports showed patients on PD had much better QOL than the HD patients.…”
Section: Discussionsupporting
confidence: 87%
“…However, their needs are never discussed or prioritized at any forum or adequately in literature [4]. In a study by Baek et al, the parents of 79 children receiving dialysis or transplant were administered a special questionnaire (Family Impact Module), and it was found that scores were worse for haemodialy sis, as compared to peritoneal dialysis or transplant [29]. In another study from Brazil by Garcia et al, 50 donors were asked to respond to the SF-36 questionnaire before and after transplantation.…”
Section: Importance Of Caregivers In Ckdmentioning
confidence: 99%